The culturally deprived child a new view - Riessman, Frank (Washington, D.C. : Distributed by ERIC Clearinghouse, 1962)
Concerned with the educational problems of children from low-income families, one must not ignore the positive efforts of low-income individuals to cope with their environment. There are positive features in the culture and the psychology of low-income individuals. A child is often slow in performing intellectual tasks for reasons other than dullness. The slow learner can be gifted and the teacher should learn not to respond only to the quick student. Second, the verbal handicap of culturally deprived children is only on a formal level, they are very good verbally under informal circumstances. The teacher should use technIQues to bring out this verbal facility. Finally, deprived children and their parents have a positive attitude toward education. They often resent school, for a number of reasons, but they do value education. Some of the weaknesses concerning deprived children that should be dealt with are general "know-how", test taking, formal language, and reading. Most of all, their anti-intellectual attitude must be changed. New school programs and new educational technIQues for teaching these children are needed.
Includes index.
Microfiche.
Keywords: Disadvantaged; Disadvantaged Environment; Educational Problems; Low Income Groups; Student Attitudes; Student Characteristics; Mobilization for Youth -- New York -- New York (New York)